CENSO DE ADULTOS MAYORES EN SITUACIÓN DE CALLE MEDELLÍN 2009 - Ruiz Restrepo, Jaime; Aigneren, Miguel (La Sociología en sus Escenarios, 2010)
Abstract. The census of third age population in street situation allows determining the proportions, to locate and to characterize this population group. To third age population in street situation, one is them in any side and comprise of the urban landscape because it is located in the markets, subway exits, streets, under bridges and churches. Nevertheless, zones exist where the third age population in street situation meet to work or simply to meet with the friendly. Those rallying points, like the Parque Berrio, "La Minorista" and bordering streets offer work possibilities to them and of sharing with the group the difficulties of the life. Given the exploratory nature of the study it is not possible to make generalization, nevertheless, which we found takes to us to reflect on the situation of the oldness in the street. The decomposition and the rupture with familiar and social bonds are present in the trajectories of life of the studied inhabitants of the street - "third age population in street situation" - We observed that the fragilities of residential, affective order, of health, exhibition to the discrimination and the violence are associate to the vulnerabilities of that population. In agreement with the previous information, the public policies directed to inhabitants of street in Medellín would have to mainly concentrate in third age population in street situation considering their greater invisibility, the greater dwell time in street and with institutional an effective support. Resumen. El catastro de personas adultas mayores en situación de calle permite dimensionar, localizar y caracterizar a este grupo poblacional. A los adultos mayores de la calle, se les encuentra en cualquier lado y forman parte del paisaje urbano debido a que se localiza en los mercados, salidas del Metro, ejes viales, bajo puentes vehiculares e iglesias. Sin embargo, existen zonas en donde los adultos mayores se reúnen para trabajar o simplemente para reunirse con los amigos. Esos puntos de reunión, como el Parque Berrío o, "La Minorista" y calles aledañas les ofrecen posibilidades de trabajo y de compartir con el grupo las dificultades de la vida. Dada la naturaleza exploratoria del estudio no es posible hacer generalizaciones, sin embargo, lo que encontramos nos lleva a reflexionar sobre la situación de la vejez en la calle. La descomposición y la ruptura con vínculos familiares y sociales están presentes en las trayectorias de vida de los habitantes de la calle estudiados - "adultos mayores" - Observamos que las fragilidades de orden habitacional, afectiva, de salud, exposición a la discriminación y a la violencia están asociadas a las vulnerabilidades de esa población.